2015
DOI: 10.1016/j.molcata.2014.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of 6-cyano-2,2-dimethyl-2-H-1-benzopyran and its subsequent enantioselective epoxidation

Abstract: a b s t r a c tThe clean synthesis of 6-cyano-2,2-dimethyl-2-H-1-benzopyran epoxide starting from 3-methyl-2-butenal is reported using recyclable catalysts. H 4 PMo 11 VO 40 (PMo 11 V) and (PyH) 3 HPMo 11 VO 40 (Py 3 -PMo 11 V) Keggin-type heteropolyacids were used to synthesize 6-cyano-2,2-dimethyl-2-H-1-benzopyran in two steps with 35% yield. This is an alternative procedure to the traditional methodology with pyridine or picoline as catalyst, where 6-cyano-2,2-dimethyl-2-H-1-benzopyran is obtained by conden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Dioxirane compounds as non-metal organic oxidants can efficiently transfer oxygen atoms to various substrates and their utility has been well known for various oxidation reactions such as epoxidation of various olefins (enol ether, silyl enol ether, 2,3-dimethylbenzofuran, enol ester, lactone and enol phosphate) [9], oxidation of sulfides, amines and carbonhydrogen bond [10]. Among them dimethyldioxirane (DMDO), known as Murray's reagent [11,12], is an oxidant used in organic synthesis and considered as an environment-friendly oxygen transfer reagent for suitable substrates without the need for a catalytic system containing transition metal [13][14][15]. However, DMDO is susceptible to decomposition especially in the presence of heat; it should be isolated at lower temperatures mostly as acetone solution.…”
Section: Introductionmentioning
confidence: 99%
“…Dioxirane compounds as non-metal organic oxidants can efficiently transfer oxygen atoms to various substrates and their utility has been well known for various oxidation reactions such as epoxidation of various olefins (enol ether, silyl enol ether, 2,3-dimethylbenzofuran, enol ester, lactone and enol phosphate) [9], oxidation of sulfides, amines and carbonhydrogen bond [10]. Among them dimethyldioxirane (DMDO), known as Murray's reagent [11,12], is an oxidant used in organic synthesis and considered as an environment-friendly oxygen transfer reagent for suitable substrates without the need for a catalytic system containing transition metal [13][14][15]. However, DMDO is susceptible to decomposition especially in the presence of heat; it should be isolated at lower temperatures mostly as acetone solution.…”
Section: Introductionmentioning
confidence: 99%
“…Within this group are pyrimidines, which are a class of six-membered heterocycles that contain two nitrogen atoms in positions 1 and 3 and are an important source for the discovery of many drugs due to their versatile properties such as anticancer, antiviral, antibacterial and insecticide activity [27][28][29][30][31][32]. This molecule can be functionalized with other biologically important molecule residues to improve its bioactivity, as in the case of 3,4-dihydropyrimidine-2 (1H) -ones (thiones), an important compound in organic synthesis due to its bioactivity [33]. The most suitable procedure for their preparation is the Biginelli synthesis, a multicomponent condensation reaction in an acid medium that involves an aldehyde, a β-dicarbonylcompound and urea or thiourea [34].…”
Section: Pyrimidinesmentioning
confidence: 99%
“…Our research group reported a green method for the synthesis of 6-cyano-2,2-dimethyl-2-H-1-benzopyran (6-CN-2,2-DMB) and its subsequent enantioselective epoxidation by the use of the heteropolyacids H 4 PMo 11 VO 40 (PMo 11 V) and (PyH) 3 HPMo 11 VO 40 (Py 3 -PMo 11 V), and homogeneous Jacobsen catalysts (Scheme 28) [33]. The reaction was carried out in three steps with a yield of 35%.…”
Section: Scheme 27 Synthesis Of Benzopyransmentioning
confidence: 99%